Pemberian Bekam Terhadap Suhu Tubuh Mahasiswi Putri Ma’had Al-Jami’ah UIN Sulthan Thaha Saifuddin Jambi - Nur Asiah Esi (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi, 2018)
This article discusses about the Influence of Cupping on Body temperature of female students at Ma'had Al-Jami'ah. This research is a quantitative research using Pre-Experimental Design and One-Group Pretest-Posttest Design. The sample in this research is female students of ma'had al-jami'ah numbering 30 people. Sampling was done by sampling purposive. With a cupping step those are a) temperature measurement before cupping b) Wet snow therapy 1 time intervention c) Measurement of Body Temperature After cupping. Research results obtained that between the body temperature before cupping and after the cupping there is a significant influence. This implies, the use of cupping can successfully lower the body temperature of female students of ma’had al-jami’ah significantly because this research uses negative correlation. Keyword: Cupping, Body temperaturve